2012
DOI: 10.1086/665823
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Patterns and Biogeochemical Significance of Angiosperm Root Traits

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
179
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(198 citation statements)
references
References 100 publications
(137 reference statements)
8
179
2
1
Order By: Relevance
“…We found a general overall pattern of root diameter becoming thinner as species diversified, similar to the pattern found in a data set of tropical and subtropical species (Comas et al. 2012). No phylogenetic signal was found in tissue density, which other studies of temperate woody species have suggested may vary more in response to soil microsite properties rather than in association with differences among species (e.g., Comas and Eissenstat 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found a general overall pattern of root diameter becoming thinner as species diversified, similar to the pattern found in a data set of tropical and subtropical species (Comas et al. 2012). No phylogenetic signal was found in tissue density, which other studies of temperate woody species have suggested may vary more in response to soil microsite properties rather than in association with differences among species (e.g., Comas and Eissenstat 2009).…”
Section: Discussionmentioning
confidence: 99%
“…2009; Comas et al. 2012). Clear evolutionary patterns are found of fine roots becoming thinner as angiosperms radiated, as compared to remaining relatively coarser in more basal and less diverse angiosperm and nonangiosoperm lineages (e.g., cycads, gnetophytes, and gingko) (Comas et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For woody plants, root diameter predominately controls differences in SRL and SSA among species, with root tissue density affecting plasticity within species due to plant responses to edaphic factors such as soil water (Comas et al, 2002; Comas and Eissenstat, 2009). Small diameter roots with greater SRL enable plants to efficiently increase hydraulic conductance by increasing surface area in contact with soil water, increasing the volume of soil that can be explored for water, and, also, increasing root hydraulic conductivity by decreasing the apoplastic barrier of water entering the xylem (Eissenstat and Achor, 1999; Rieger and Litvin, 1999; Huang and Eissenstat, 2000; Solari et al, 2006; Hernández et al, 2010; Comas et al, 2012). Accordingly, decrease in root diameter has been proposed as a trait for increasing plant acquisition of water and productivity under drought (Wasson et al, 2012).…”
Section: Root Systems Traits and Functioning In Water Uptakementioning
confidence: 99%
“…Similarly, differences in fine‐root traits among species are thought to represent their evolutionary history and adaptations to a wide range of biotic and abiotic factors (Kembel & Cahill ; Comas et al . ).…”
Section: Introductionmentioning
confidence: 97%